Micro-RNA (miRNA): A Biomarker to Identify Novel Compounds in Drug Discovery and Delivery for Cancer Therapy - Paramasivam, Gokul (Current Drug Discovery Technologies, 2021)
Micro-RNAs (miRNA) are short non-coding sequences involved in the biological regulatory process. The miRNAs show a unique expression in diseases, resulting in pathogenesis. Identifying the novel compounds is interesting during this process. The miRNA is a biomarker that helps to detect cancer at an early stage through pathogenesis. Azobenzene and pyrazole are novel compounds, having a cytotoxic effect on cancer cells. These novel compounds are molecular probes used in breast cancer therapy. The viral-based systems have few limitations, such as toxicity and immunogenicity. Therefore, the non-viral based lipoplex and polyplex systems are attractive due to no size limitations for the transfection of micro RNAs. The conventional drug delivery systems have a large size and low drug efficacy at the target site. The nanoparticles prepared by nanoprecipitation methods are attractive in cancer therapy. Thus, the miRNA acts as a powerful tool and identifies the drug target in cancer therapy.
Keywords: drug discovery